Cloudy or sunny? Effects of different environmental types of urban green spaces on public physiological and psychological health under two weather conditions - Cao, Saixin; Shang, Zike; Li, Xi; Luo, Hao; Sun, Lingxia; Jiang, Mingyan; Du, Juan; Fu, Erkang; Ma, Jun; Li, Nian; Guo, Baimeng; Yu, Xiaofang; et al. (Frontiers in Public Health, 2023)
Numerous studies have demonstrated that urban green spaces (UGSs) benefit human health, but few have focused on the influence of weather on environmental restorativeness. This study assessed how different weather conditions and environments affect human health. We exposed 50 participants to different UGS environments under cloudy and sunny conditions and collected physiological, psychological and aesthetic preference data. The result showed that the physical and mental benefits of UGSs were stronger on sunny days (pulse: [t = 2.169, p < 0.05]; positive affect: [Z = −10.299, p < 0.001]; perceived restortiveness: [Z = −3.224, p < 0.01]). The spaces with exposed sky had greater physiological restorativeness on sunny days; the spaces with calm water had greater emotional restorativeness on cloudy days, and natural spaces with less sky exposure had greater perceived restoration in both weather conditions. The spaces with water and less sky exposure promoted psychophysiological restoration in both weather conditions. This study demonstrates that weather significantly influences the restorative potential of UGSs, and there are also restorative variations in different green space environments under two weather conditions. In future UGS planning practices, it would be advisable to select appropriate environmental types and features based on the climatic characteristics of different regions. For instance, in areas with frequent overcast conditions, incorporating serene water bodies could be advantageous, while regions with predominantly sunny weather should encompass spaces with expansive sky views. By conducting comprehensive research on restoration environments that take weather conditions into account, new insights and nature-based solutions can be provided for creating healthy human habitats in the context of global climate change.